Does Increasing the Experiential Component Improve Efficacy of the "This Is Public Health" Photo Essay Task? A Nonrandomized Trial. (September 2019) - Dundas, Kate; Johnson, Natalie A.; Paras, Lorraine; Hancock, Stephen; Barker, Daniel; Chiu, Simon; James, Erica L.
Opportunities for evaluating experiential learning activities in tertiary public health education are growing. It has previously been shown that utilizing the "This is Public Health" (TIPH) sticker campaign as an experiential photo essay task led to increased understanding of public health. Emerging mobile technologies such as geocaching, which provide an opportunity to increase the experiential component of the TIPH photo essay task, have not been evaluated. This study aimed to determine whether adding geocaching to the TIPH photo essay task increased the efficacy of learning about public health, when compared with the TIPH photo essay task alone. A two-arm nonrandomized trial was conducted with 785 allied health and preprofessional teaching students studying first-year public health courses. Students were allocated to either the TIPH photo essay task ( n = 210) or the TIPH photo task plus geocaching ( n = 92) according to the course they were enrolled into. The primary outcome was the quality of the definition of public health provided by students, which was assessed using the Definition of Public Health Rating Scale. Data were analyzed using a linear mixed model. Of 302 (39%) students who consented to participate, 212 (70%) provided baseline and follow-up data. After adjusting for baseline demographic differences, the geocaching group had improved knowledge of public health at follow-up according to the Definition of Public Health Rating Scale (increasing 0.29 units more than the traditional group; p = .03). As this increase in knowledge score is unlikely to be of practical significance, the additional burden of implementing geocaching may not be justified.